PP.47 Evaluating Outcomes of Skeletal Dysplasias (SDs). (26th April 2013) - Perry, PD; Budd, JLS; Draper, ES
Abstract : Objective: To evaluate the outcome of 543 pregnancies identified with a skeletal dysplasia or an antenatal suspected skeletal anomaly in the East Midlands and South Yorkshire (EMSYCAR) Congenital Anomaly Register over a fifteen year period. Background: Skeletal dysplasias form a large group of congenital anomalies affecting cartilage and bone growth. Strongly associated with syndromes and underlying genetic conditions, they vary in severity from lethal achondroplasias to milder osteochondroplasias. The UK Fetal Anomaly Screening Programme antenatal detection target for lethal SDs is 60%. Given the problems with definitive antenatal diagnosis this is difficult to achieve. Methods: Between 1997 and 2011, 982, 073 births were monitored by EMSYCAR; 543 cases were identified with a SD or antenatally suspected skeletal anomaly (a birth prevalence of 5.53/10, 000 births). Each case was individually reviewed to ascertain the type and severity of the skeletal anomaly as ICD-10 codes alone cannot adequately perform this function. Results: 62 (11.4%) of the 543 had fully resolved by delivery. 77 (18.4%) resulted from a chromosomal anomaly, and 65 (12.0%) had other structural anomalies. The remaining 339 (62.4%) had a skeletal anomaly (3.45/10, 000), of which 206 had a SD . Of these 77 were non-lethal and 129 lethal (1.31/10, 000). Overall, 93% of lethal SDs were identified antenatally, 63% within the FASP screening window (<20+6 weeks gestation). Conclusion: Although only 38% of total cases had an isolated actual or suspected skeletal anomaly, almost two-thirds of those were lethal SDs. The vast majority were antenatally diagnosed and the FASP target achieved.